A Study Of Self-Care Behavior In Patients Post Kidney Transplantation In Northeast Region - แสงสวย อิสริยาภรณ์; นาวีเจริญ รุ้งระวี (Journal of The Royal Thai Army Nurses, 2019)
This descriptive research aimed to study self-care behaviors in patients with post kidney transplantation at northeast region. The sample consisted of 120 participants were recruited by using Simple random sampling, aged between 18 to 59 year olds, received treatment at the tertiary care setting, Ministry of Public Health in northeast region, Thailand. The Research instrument included of 2 parts: 1) a demographic information sheet 2) a Self-care behaviors in post kidney transplantation questionnaire was based on Nursing theory of self-care (Orem,2001). Internal consistency, reliability determined by Cronbach’s alpha coefficients was 0.85. Data were analyzed using frequency, percentage, mean, standard deviation. The major findings were presented as follows: the mean of Developmental self-care requisites in patients with post kidney transplantation were highest level (Mean = 4.71, SD = 0.53).